Prove that :(secA+tanA)(1−sinA)=cosA View Solution Prove that :cosA1+sinA+1+sinAcosA=2secA View Solution Free Ncert Solutions English Medium NCERT Solutions NCERT Solutions for Class 12 English Medium NCERT Solutions for Class 11 English Medium ...
Prove that : (i) (1)/(1-cosA)+(1)/(1+cosA)=2"cosec"^(2)A " " (ii) (1)/(1-sinA)-(1)/(1+sinA)=2secAtanA
Step by step video & image solution for Prove : (sinA+cosecA)^(2)+(cosA+secA)^(2)=7+tan^(2)A+cot^(2)A. by Maths experts to help you in doubts & scoring excellent marks in Class 10 exams. Updated on:21/07/2023 Class 10MATHSTRIGONOMETRIC RATIOS AND IDENTITIES ...
Prove that :(secA+tanA)(1−sinA)=cosA View Solution Porve that : (cosecA-sinA)(secA-cosA)=1tanA+cotA View Solution Free Ncert Solutions English Medium NCERT Solutions NCERT Solutions for Class 12 English Medium NCERT Solutions for Class 11 English Medium ...